Inhibition of CLIC4 Enhances Autophagy and Triggers Mitochondrial and ER Stress-Induced Apoptosis in Human Glioma U251 Cells under Starvation - Zhong, Jiateng; Kong, Xiaoxia; Zhang, Hongyu; Yu, Chunyan; Xu, Ye; Kang, Jinsong; Yu, Huimei; Yi, Haowei; Yang, Xiaochun; Sun, Liankun (PLOS ONE, 2012)
CLIC4/mtCLIC, a chloride intracellular channel protein, localizes to mitochondria, endoplasmic reticulum (ER), nucleus and cytoplasm, and participates in the apoptotic response to stress. Apoptosis and autophagy, the main types of the programmed cell death, seem interconnected under certain stress conditions. However, the role of CLIC4 in autophagy regulation has yet to be determined. In this study, we demonstrate upregulation and nuclear translocation of the CLIC4 protein following starvation in U251 cells. CLIC4 siRNA transfection enhanced autophagy with increased LC3-II protein and puncta accumulation in U251 cells under starvation conditions. In that condition, the interaction of the 14-3-3 epsilon isoform with CLIC4 was abolished and resulted in Beclin 1 overactivation, which further activated autophagy. Moreover, inhibiting the expression of CLIC4 triggered both mitochondrial apoptosis involved in Bax/Bcl-2 and cytochrome c release under starvation and endoplasmic reticulum stress-induced apoptosis with CHOP and caspase-4 upregulation. These results demonstrate that CLIC4 nuclear translocation is an integral part of the cellular response to starvation. Inhibiting the expression of CLIC4 enhances autophagy and contributes to mitochondrial and ER stress-induced apoptosis under starvation.